Mobbing and its impact on health of nurses – a pilot study - Václavíková, Klára; Kozáková, Radka (Nursing in the 21st Century, 2021)
MOBBING AND ITS IMPACT ON HEALTH OF NURSES – A PILOT STUDY Aim. The aim of this study was to determine the occurrence of mobbing and its health impacts on nurses in the selected hospital. Method. The pilot study was performed from August to September 2020. The group consisted of 84 nurses (return was 56.0%), working in the acute care department in a selected medical facility. NAQ-R (Negative Acts Questionnaire-Revised) and GHQ-28 (General Health Questionnaire-28) tools were used. Results. In total 10.50% of nurses experienced mobbing. Mobbing was targeted at the work-oriented and nurse-related areas. The most common descriptive phenomenon of mobbing is the assignment of tasks below the level of competencies. Nurses describing the occurrence of mobbing in the workplace more often reported feelings of constant tension, nervousness and pressure. Conclusions. The occurrence of mobbing in the workplace can affect the health and cause mental and social problems of nurses.